What was the Tulsa Race Massacre of 1921? - Gayle, Caleb; Foley, Tim, 1962- (New York : Penguin Workshop, 2023)
Before May 31, 1921, the Greenwood District of Tulsa, Oklahoma, was a thriving neighborhood of 10,000 Black residents. There, Black families found success and community. They ran their own businesses, including barbershops, clothing stores, jewelers, restaurants, movie theaters, and more. There also were Black doctors, dentists, and lawyers to serve the neighborhood. Then, in one weekend, all of this was lost. A racist mob tore through the streets, burning everything to the ground and killing scores of innocent residents. Learn about what led to one of the worst moments of racial violence in America's history in this nonfiction book for young readers.
What was the Tulsa Race Massacre of 1921? -- The promise of Oklahoma -- Danger! -- The deadly spark -- The shot heard 'round Tulsa -- The invasion of Greenwood -- Nothing left? -- No help -- Greenwood rises again -- Urban renewal ... really? -- The story lives on -- Timelines.
Includes bibliographical references (pages 106-107).
4.6
3-6
960L
Keywords: Tulsa Race Massacre, Tulsa, Okla., 1921 -- Juvenile literature; African Americans -- Oklahoma -- Tulsa -- History -- 20th century -- Juvenile literature; Riots -- Oklahoma -- Tulsa -- History -- 20th century -- Juvenile literature; Racism -- Oklahoma -- Tulsa -- History -- 20th century -- Juvenile literature; Tulsa (Okla.) -- Race relations -- Juvenile literature; Greenwood (Tulsa, Okla.) -- Race relations -- Juvenile literature; Tulsa Race Massacre, Tulsa, Okla., 1921.; African Americans -- Oklahoma -- Tulsa -- History -- 20th century; Riots -- Oklahoma -- Tulsa -- History -- 20th century; Racism -- Oklahoma -- Tulsa -- History -- 20th century; Tulsa (Okla.) -- Race relations; Greenwood (Tulsa, Okla.) -- Race relations